Solar Water Heaters in Cyprus: Manufacturing, Performance and Applications - Kalogirou, Soteris A. (My University, 2005)
This paper reviews the application of solar water heating in Cyprus. The full reliance of Cyprus on imported oil to meet its energy demand, together with the abundance of solar radiation and a good technological base, created favourable conditions for the exploitation of solar energy in the island. Initially the Cyprus energy scene is presented and analysed with emphasis on the contribution of solar energy to the total energy consumption. From this analysis it is shown that 4.5% of the annual energy demand of Cyprus is provided from solar energy. This energy is used mainly in the domestic sector (93.5%) for hot water production. Additionally, 80% of the hotel apartments and 44% of the hotels are equipped with central solar water heating systems. One of the most widely used systems for domestic water heating is the solar thermosyphon unit. A description of the characteristics and manufacture of thermosyphon units is presented followed by a study on the performance characteristics and environmental protection offered by the systems. Such a system is modeled with TRNSYS and the results show that the system can provide 7225 MJ of energy per year and the solar contribution is 85%. The financial characteristics of the system investigated give life cycle savings, representing the money saved because of the use of the system throughout its life instead of using electricity, equal to 1120 Euro and pay-back time equal to 4 years. Life cycle analysis shows that by using solar energy considerable amounts of greenhouse polluting gasses are avoided. The saving, compared to a conventional system with electricity backup, is about 80% and the pollution created for the production of the system is recouped in about 1.2 years. It can therefore be concluded that solar energy systems offer significant protection to the environment and cost savings and should be employed whenever possible in order to achieve a sustainable future.
Keywords: Solar water heating; Cyprus